First reports of Myotis riparius (Chiroptera: Vespertilionidae) in the high-Andes southern Ecuador - Nivelo-Villavicencio, Carlos Hernán (2020)
The Vespertilionidae family is widely distributed in South America. In Ecuador, there are 20 species including Myotis riparius. The species has been recorded between 10 to 1240 m a.s.l. on the both eastern and western sides of the Andes cordillera. In this work we reported two new localities for southern Ecuador which include the highest records for the species and increasing in 1077 m the limit elevation previously known in Ecuador.